Ancient stepmothers : myth, misogyny, and reality - Watson, Patricia A., 1947- (Mnemosyne, Supplements, 1995)
Ancient Stepmothers is the first full-length study of the stepmother in Graeco-Roman antiquity. Several perspectives are covered: literary, historical and sociological, the last-mentioned making use of comparative material from modern studies of stepfamilies. The portrayal of the stepmother in myth and literature is thoroughly explored. The historical background in Athens and Rome is examined with a view to determining the relationship between fiction and real life. The book makes an important contribution to the study of both literary history and family relationships: in particular, it sheds light on attitudes to women, the portrayal of the stepmother being an outstanding illustration of misogynistic prejudice. It will also interest sociologists wishing to place studies of the contemporary stepfamily in a wider historical context: for this reason, all Greek and Latin is translated into English.